Hermeneutic Literature Review: A Methodological Possibility in Organizational Studies - Faganello, Cláucia; Hamerski, Bruna; Moraes Pinheiro, Daniel (Organizações & Sociedade, 2025)
In the context of increasingly complex organizational dynamics, there is a growing need to deepen and refine research methods. Hermeneutics provides an iterative, dynamic, interpretive, and critical framework for conducting literature reviews. This paper offers an overview of how this method is applied in organizational studies. It starts by introducing the main concepts related to the method, followed by an application protocol and a summary of key studies that have used it. The analysis highlighted that the hermeneutic method provides a unique approach to understanding literature, as it is dynamic, comprehensive, and critical, with a specific focus on interpreting meanings and their temporal evolution. However, the method is still underused in the organizational field. The study demonstrated the feasibility of applying this methodology and encourages further exploration within organizational studies. As a research agenda, it is recommended to expand the search to encompass the broader field of administration and incorporate additional academic databases.